Working with coaches and their teams in youth and collegiate sport in the USA: An interview with Dr Andy Gillham - Commentary - Gearity, B. T. (International Journal of Sports Science & Coaching, 2018)
Storyteller sharing morality and purpose. As a consultant. Andy navigates the realities of many and varying theoretical Frameworks, personnel. and contexts. He has experience as a coach. coach developer. researcher, and mental skills trainer for athletes. He's able to blend in on the bench or in the Stands, change his communication style based on the audience, and recognizes that real-life problem-solving requires critical thinking that can draw upon, but also extend and diverge from, existing theory or research. I'm housed in a graduate school of Professional psychology and one of the concepts my colleagues here introduced to me is the "scholar-practitioner model." which means we employ scholar-psychologists, somebody who is well versed theoretically and our students are immediately imjjj practitioner model also means while taking courses and receiving extensive mentoring from faculty. Without the same model so well established in sport training programs. Andy's ,, the scholar-practitioner model. I want to claborate on this interesting point within the context of sport in American(USA) society. and secondarily internationally.